Stability criterion of compound amplifier - Singh A. (My University, 2025)
A study is made of the conditions for a stable amplifying operation of the compound system of combinations JJ, JP, PJ and PP in all the three configurations. The expressions for the minimum values of load resistance and generator resistance required to compensate the negative resistances in the input and output are also derived. © 1973 Taylor & Francis Group, LLC.